Empowering students, enhancing communities: Integrating Service-Learning as a character education methodology in a Chilean school - Moller, Francisco; Redondo-Corcobado, Paloma; Fuentes, Juan Luis (Journal of Moral Education, 2026)
This study explores the potential of Service-Learning (SL) to foster the virtues of empathy and civic engagement among Chilean secondary students. Conducted in a single all-male public school, the intervention consisted of eight classroom sessions and a brief community implementation phase. While overall pre- and post-survey comparisons showed no significant cohort-wide changes, students from two-parent households demonstrated increased empathy, and low-performing students exhibited gains in both empathy and civic engagement. These results suggest that SL may hold particular promise for students who are often overlooked in traditional academic settings. Qualitative focus groups offered further insight, revealing instances of moral reflection and enhanced empathy, supporting the view that SL can contribute to integrating moral and civic education. Although preliminary, these findings point to SL’s potential as a character education methodology, warranting further research into its long-term impact and broader applicability across diverse educational contexts.
Keywords: service-learning; character education; civic engagement; empathy